Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1038/jcbfm.2008.79
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection in Diet-Induced Ketotic Rat Brain after Focal Ischemia

Abstract: Neuroprotective properties of ketosis may be related to the up-regulation of hypoxia inducible factor 1 (HIF-1α), a primary constituent associated with hypoxic angiogenesis and a regulator of neuroprotective responses. The rationale that the utilization of ketones by brain results in elevation of intracellular succinate, a known inhibitor of prolyl-hydroxylase (the enzyme responsible for the degradation of HIF-1α) was deemed as a potential mechanism of ketosis on the up-regulation of HIF-1α. The neuroprotectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
122
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 45 publications
4
122
1
Order By: Relevance
“…43,44 In addition, it has recently been shown that the ketogenic diet and the infusion of BHB stabilize the hypoxia induced factor, which regulates the expression of genes involved in energy metabolism and antiapoptotic proteins such as Bcl-2. 7 It remains to be investigated whether these mechanisms are involved in the protective effect of BHB observed in the present experimental conditions. β-hydroxybutyrate reduces ROS during hypoglycemia A Julio-Amilpas et al…”
Section: Discussionmentioning
confidence: 88%
“…43,44 In addition, it has recently been shown that the ketogenic diet and the infusion of BHB stabilize the hypoxia induced factor, which regulates the expression of genes involved in energy metabolism and antiapoptotic proteins such as Bcl-2. 7 It remains to be investigated whether these mechanisms are involved in the protective effect of BHB observed in the present experimental conditions. β-hydroxybutyrate reduces ROS during hypoglycemia A Julio-Amilpas et al…”
Section: Discussionmentioning
confidence: 88%
“…This process is not well understood but is thought to be highly associated with the duration and level of ketosis. 10,19,37,38 Ketones are considered to supply up to 70% of the total energy demands once maximal metabolic adaptation occurs. 1 Blood ketones become elevated during prolonged fasting or with a ketogenic diet reaching a state ketosis and glucose sparing.…”
Section: Discussionmentioning
confidence: 99%
“…16 Ketone bodies as neuroprotective agents appear to be related to the change in the regulation of the cell's stress responses, 17 as well as changes in oxidative (glucose) metabolism. 18,19 Neuroprotection by ketosis is thought to be associated with improved mitochondrial function, decreased reactive oxygen species, apoptotic and inflammatory mediators, and protective pathways. 9,20 In the last few decades, the 2-deoxy-D-glucose or positron emission tomography (PET) approaches have been applied to ketotic studies, in both animal, 18,[21][22][23] and humans.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, ketogenic diet is now established in the treatment of pharmacoresistant childhood epilepsy. In addition, ketogenic diet and BHB exert a protective function in animal models of stroke, PD, AD and ALS [4][5][6][7][8] . So far small clinical trials suggest that it is also effective in neurodegenerative diseases 9 .…”
mentioning
confidence: 99%